Fresno County Young Lawyers Hopper Luncheon Keynoter California Supreme Court Associate Justice Malcolm Lucas - Watkins, Howard::::::::: (1985)
Jim Christiansen, former law clerk to Justice George Hopper, sharing some history about Hopper